2020
DOI: 10.20944/preprints202004.0515.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobility Restrictions and Air Quality under COVID-19 Pandemic in São Paulo, Brazil

Abstract: Social distancing policies put in place during COVID-19 epidemic in addition to helping to limit the spread of the disease also contributed to improving urban air quality. Here we show a decrease in air pollutant concentration as a consequence of mobility reduction in São Paulo during the containment measure which began on 22nd March 2020. When comparing to foregoing weeks to equivalent periods of 2019, the concentration of most air pollutants sharply decreased in the first days of mobility restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
4
7
0
1
Order By: Relevance
“…In addition, both analyzed periods showed similarity in terms of atmospheric pressure (on average, approximately 927 hPa), global solar radiation (on average, approximately 677 W/m 2 ) and relative humidity (mean close to 47%) [34]. Therefore, based on these observations, the control period demonstrated meteorological conditions similar to those observed during the quarantine period, justifying the selection of 2019 as a control period, as previously reported in published studies related to the analysis of air pollution during the ongoing COVID-19 pandemic [39,40].…”
Section: Methodssupporting
confidence: 73%
“…In addition, both analyzed periods showed similarity in terms of atmospheric pressure (on average, approximately 927 hPa), global solar radiation (on average, approximately 677 W/m 2 ) and relative humidity (mean close to 47%) [34]. Therefore, based on these observations, the control period demonstrated meteorological conditions similar to those observed during the quarantine period, justifying the selection of 2019 as a control period, as previously reported in published studies related to the analysis of air pollution during the ongoing COVID-19 pandemic [39,40].…”
Section: Methodssupporting
confidence: 73%
“…Research groups in major cities such as Sao Paulo, Brazil; Wuhan, China; and Barcelona, Spain reported decreases in traffic-related air pollutant concentrations from January to May 2020 (Abdullah et al, 2020;Cadotte, 2020;Kambalagere, 2020;Li et al, 2020;Tobías et al, 2020;Zambrano-Monserrate et al, 2020;Zheng et al, 2020), which they suggest is a result of reduced vehicle emissions. Several studies have also shown similar reductions in pollutant concentrations by comparing 2020 concentrations to those measured in previous years (Chen et al, 2020;Dantas et al, 2020;Dutheil et al, 2020;Freitas et al, 2020;Isaifan, 2020;Muhammad et al, 2020;Nakada and Urban, 2020;Sharma et al, 2020;Xu et al, 2020). Similar work has been completed in the US, but to a much lesser extent (Berman and Ebisu, 2020;EarthSky Team, 2020;Muhammad et al, 2020;Porterfield, 2020;Stein, 2020;Volcovici, 2020).…”
Section: Introductionmentioning
confidence: 67%
“…Consequently, air pollution levels dropped during the quarantine. For instance, the concentrations of carbon monoxide (CO), nitrogen dioxide (NO 2 ), PM 10, and PM 2.5 were reduced by −35.70%, −29.56%, −17.80%, and −25.02%, respectively, while O 3 increased by 53.25% between 21:00–03:00 Local Time (LT) ( Dantas et al, 2020 ; Freitas et al, 2020 ; Nakada and Urban, 2020 ). Other studies showed reductions in China (30% of NO 2 and 25% of CO 2 ) ( Dutheil et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%